Transcriptomics of iron limitation in Phaeocystis antarctica - Issak, Mariam Reyad Rizkallah (AUC Knowledge Fountain, 2014)
Phytoplankton, the hidden trees of the ocean, are responsible for nearly half of global oxygen production. Phytoplankton growth and productivity in high-nitrate low-chlorophyll (HNLC) regions have been demonstrated to be limited by iron availability. One of the most important HNLC regions is the Southern Ocean, as it regulates Earth system climate due to its unique hydrography and consequently its phytoplankton assemblage drives the global carbon cycle. Iron fertilization experiments were conducted to understand the response of its photosynthetic assemblage to iron addition, and the nanoflagellate Phaeocystis antarctica has been reported the first to bloom. P. antarctica is ecologically important due to its contribution in global sulfur gases emissions. Thus, P. antarctica fits as an ideal model organism in understanding phytoplankton adaptation to iron limitation and functional changes following iron addition. Here the results of a transcriptomic study assessing the effect of iron repletion on P. antarctica in a time-series manner are firstly reported. A Ross Sea-endemic P. antarctica clone was acclimated under iron limitation and iron was supplemented to the cultures. RNA was extracted at 5 time-points before and after iron addition. The generated 389,846,414 paired-end Illumina reads were de novo assembled into ~88,000 putative genes, providing the first reported transcriptome of P. antarctica. Differential expression at each time-point was inferred at an adjusted p-value ≤ 0.001 and a log fold-change ≥ 5, revealing a total of 2,367 differentially expressed genes. Iron-limited P. antarctica recovered its photosynthetic fitness, colony-forming ability, and chlorophyll a, particulate organic carbon and nitrogen contents shortly after iron addition comparable to the replete control and the reported values of healthy cells. A shift in expression from iron-economic reactive oxygen species defense and photosystem II to iron-dependent alternatives has been observed. In addition, a metabolic shift from structural carbon and nitrogen reallocation to anabolism has been observed. Transcriptomic data supports the previous studies that P. antarctica is successful in utilizing bound iron in a reductive non-ligand-dependent mechanism. Iron levels limits P. antarctica growth yet its iron requirements are the lowest among all phytoplankton species and its adaptation to iron limitation is well-established.